A kind of sulphoaluminate cement repair material and preparation method thereof
By using sodium gluconate and ultrafine powder to adjust the settling time in the sulfa aluminate cement repair materials, the problems of high raw material costs and later strength reversal in the existing sulfa aluminate cement repair materials are solved, and the low material is achieved Cost, efficient preparation and excellent performance.
Patent Information
- Application Number
- CN202311166811.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-09-11
Smart Images

Figure CN117361988B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cement admixtures, and in particular relates to a sulphoaluminate cement repair material and a preparation method thereof. Background Art
[0002] Cement mortar and concrete have been widely used around the world due to their excellent mechanical properties and durability. Since the last century, mortar and concrete infrastructure has been developed considerably around the world. However, due to the long-term exposure of building structures to the natural environment, the erosion of the harsh environment and the action of mechanical external forces, local damage is prone to occur, which accelerates erosion damage and reduces the service life of the building structure. In order to avoid further development of structural damage, the usual practice is to remove the damaged part and use repair materials for repair and reinforcement.
[0003] At present, the research focus of the field of repair and protection is on the repair and reinforcement of important infrastructure and other urban buildings. In recent years, with the development of economic construction, a large number of building structures have inevitably suffered structural damage due to the increase in service time, shortening their service life. However, the repair and reinforcement of existing building structures in villages and towns such as masonry structures, brick-concrete structures and low-grade concrete structures (≤C30) have not been taken seriously. A large number of building structures need to be repaired and reinforced, and the demand for repair materials can be imagined.
[0004] It can be seen that there is a huge market demand for repair materials suitable for existing buildings in villages and towns. Common repair materials on the market now mainly include: (1) polymer repair materials, commonly high molecular weight resin polymers such as epoxy resin and polyester resin; (2) cement-based repair materials with special cements such as sulfoaluminate cement and magnesium phosphate cement as the main binder. Compared with expensive polymer repair materials, special cement repair materials are more widely used due to their low price, excellent performance and good compatibility with matrix structures such as mortar and concrete. Unlike flexible pavements, once local damage occurs on cement concrete pavements, if it is not handled in time, it will cause very serious consequences and cause huge economic and social losses.
[0005] Among them, the calcination temperature required for the production of sulphoaluminate cement is low and less calcium raw materials are needed, and its CO2 emissions can be reduced by 50% to 85%. In addition, due to its excellent properties such as rapid solidification, rapid development of early strength, frost resistance, low shrinkage or micro expansion and corrosion resistance, sulphoaluminate cement is widely used in special fields such as road repair, high-altitude cold environment construction, emergency repair and construction, seawater erosion resistance and ultra-high performance concrete. Although it has been used in construction for many years, sulphoaluminate cement still has many problems, such as high raw material cost, shrinkage in late strength, concentrated hydration heat release, difficult to control setting time, poor compatibility with admixtures, etc. These problems restrict the widespread use of sulphoaluminate cement in actual engineering fields to a certain extent.
[0006] For example, the patent with application number 201510475045.9 proposes a retarder suitable for sulphoaluminate cement, which is composed of the following raw materials in parts by weight: 7-60 parts of urea, 3-11 parts of sodium lignin sulfonate, 2-7 parts of sodium dinaphthylmethane disulfonate, 2-5 parts of water reducer, and 30-70 parts of vermiculite. Although the retarder can effectively delay the setting speed of sulphoaluminate cement, significantly improve the fluidity of sulphoaluminate cement paste, and reduce the demand for water when mixing sulphoaluminate cement, the cost of raw materials required in the preparation process of the retarder is relatively high. The patent with application number 201711440073.2 proposes a retarder suitable for sulphoaluminate cement. The initial setting time of the prepared sulphoaluminate cement retarder can be extended to 76 minutes, and the final setting time is 103 minutes, but the setting time still does not meet the demand, etc.
[0007] Ultrafine mineral admixture is an ultrafine powder with high volcanic ash activity, referred to as "ultrafine powder". After the material is ultrafinely processed into ultrafine powder, in addition to having a huge specific surface area and surface energy, its mechanical, thermodynamic and surface and interface properties will also undergo strange changes, and when added to the material for use, it often produces unexpected effects. Based on this, the present invention proposes a new type of sulphoaluminate cement setting regulator. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a sulphoaluminate cement repair material and a preparation method thereof.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] One of the technical solutions of the present invention is a sulphoaluminate cement repair material, the raw materials of which include sulphoaluminate cement, sodium gluconate and superfine powder, wherein the mass ratio of sulphoaluminate cement to superfine powder is (7-9): (1-3), and sodium gluconate accounts for 0.05%-0.25% of the total mass of sulphoaluminate cement and superfine powder.
[0011] Furthermore, the mass ratio of the sulphoaluminate cement to the ultrafine powder is 7:3, and the sodium gluconate accounts for 0.25% of the total mass of the sulphoaluminate cement and the ultrafine powder.
[0012] Furthermore, the raw materials of the sulphoaluminate cement repair material also include water, and the amount of water used is 50% of the total mass of the sulphoaluminate cement and the ultrafine powder.
[0013] Furthermore, the specific surface area of the ultrafine powder is 700-900m 2 / kg, median diameter ≤5μm.
[0014] Furthermore, the components of the ultrafine powder include CaO, SiO2, Al2O3, Fe2O3, SO3, MgO, TiO2, P2O5, K2O and Na2O.
[0015] Furthermore, the raw materials of the ultrafine powder include mineral powder, fly ash and gypsum.
[0016] Furthermore, the preparation method of the ultrafine powder is a ball mill ultrafine powder grinding and air separation process, specifically: the raw material ore powder, fly ash and gypsum are transported to the ultrafine ball mill by an elevator for grinding, and a dust collector is provided at the outlet of the ultrafine ball mill to collect dust; the ground material is sent to the powder separator by the elevator for powder selection, and the specific surface area is 700-900m 2 / kg of finished ultrafine powder is collected by the powder collector and sent to the finished product elevator for storage through the air chute; the unqualified fine powder returns to the ultrafine ball mill entrance from the bottom outlet of the powder selector through the air chute and re-enters the ball mill for grinding until it is ground into qualified ultrafine powder.
[0017] The second technical solution of the present invention is a method for preparing the sulphoaluminate cement repair material, comprising the following steps:
[0018] Weigh the required sulphoaluminate cement, sodium gluconate, superfine powder and water according to the mass ratio, dissolve the sodium gluconate in water to obtain a sodium gluconate solution, mix the superfine powder and sulphoaluminate cement evenly, add them to the sodium gluconate solution, stir evenly, and obtain the sulphoaluminate cement repair material.
[0019] The sulphoaluminate cement repair material of the present invention has sulphoaluminate cement as the main component, sodium gluconate is used to adjust the reaction speed of sulphoaluminate cement, and superfine powder is used to increase the strength of cement and the setting time of sulphoaluminate cement. The present invention aims to reduce the preparation cost of silicon-alumina cement-based repair mortar while improving the setting time of the repair material. The superfine powder is used as an admixture to prepare a repair material with adjustable setting time. Compared with the prior art, the present invention has the following advantages and technical effects:
[0020] (1) The present invention mixes ultrafine powder and sulphoaluminate cement in different proportions, and adjusts the amount of ultrafine powder and sodium gluconate to adjust the setting time of sulphoaluminate cement, thereby achieving further regulation and control, thereby making the use scenarios of silicon-alumina cement-based repair materials more diversified.
[0021] (2) The ultrafine powder prepared by the present invention by controlling the mill process technical parameters and the raw material ratio has the characteristic of adjustable fineness, which can realize the efficient industrial production of ultrafine powder and reduce the preparation cost of the repair material.
[0022] (3) The ultrafine powder of the raw material of the sulphoaluminate cement setting regulator of the present invention has a particle size of micrometer level and a high specific surface area, which can form a micro-grading effect with the sulphoaluminate cement, improve the structure of the silicoaluminate cement-based repair material, increase the density and homogeneity of the repair material, and enhance the construction performance and water retention of the repair mortar.
[0023] (4) The ultrafine powder of the present invention has high pozzolanic activity and can undergo secondary chemical reaction with cement hydration products. It has low hydration exotherm, improves the hydration degree of cement stone, and promotes the continuous growth of cement strength in the later stage.
[0024] (5) The present invention utilizes ultrafine powder and sulfoaluminate cement and sodium gluconate powder materials to form a micro-grading effect, thereby improving the density and homogeneity of silicon-aluminum repair materials, reducing the porosity of the repair mortar, and improving the microstructure of the repair mortar; the hydration exotherm is low; the ultrafine powder and the hydration product of sulfoaluminum cement can undergo a secondary chemical reaction, thereby improving the hydration degree of cement stone and promoting the subsequent sustained growth of cement strength; the ultrafine powder particles have a submicron size, a high specific surface area, good water retention and homogeneity, no segregation, no water seepage, and improves the construction performance of sulfoaluminum cement mortar repair materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0026] Figure 1 A bar chart comparing the initial setting and final setting times of each sample prepared in the examples;
[0027] Figure 2 This is the SEM microscopic morphology of the raw material sulphoaluminate cement at 5000 times magnification;
[0028] Figure 3 The SEM microscopic morphology of the raw material sulphoaluminate cement at 1000 times magnification;
[0029] Figure 4 This is the SEM microscopic morphology of the raw material ultrafine powder magnified 5000 times;
[0030] Figure 5 This is the SEM microscopic morphology of the raw material ultrafine powder at 1000 times magnification;
[0031] Figure 6 is the particle size distribution curve of the raw material sulphoaluminate cement;
[0032] Figure 7 is the particle size distribution curve of the raw material ultrafine powder;
[0033] Figure 8 The porosity measurement results of the repair materials 28d of samples 7, 8, 10 and 11 prepared in the examples;
[0034] Fig. 9 The results of the determination of the effects of the samples prepared in Examples 13-16 on the cement hydration heat release (a) and the hydration heat release rate (b);
[0035] Fig.10 These are the compressive strength test results of the repair materials of Samples 7, 8, 10 and 11 prepared in Examples. DETAILED DESCRIPTION
[0036] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0037] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0038] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0039] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0040] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0041] The embodiments of the present invention and the performance testing process are all carried out in the laboratory of Jinan University.
[0042] The cement used in the embodiment of the present invention is sulphoaluminate cement specified in the Chinese national standard GB / T 37125-2018.
[0043] The ultrafine powder raw materials used in the embodiment of the present invention include mineral powder, fly ash and gypsum, which are produced by the institution affiliated to Jinan University and have a specific surface area of 700-900m 2 / kg, median diameter ≤5μm. The specific mass percentages of the ultrafine powder components used in the embodiments of the present invention are shown in Table 1:
[0044] Table 1 Ultrafine powder composition mass percentage
[0045]
[0046] Unless otherwise specified, the "parts" used in the embodiments of the present invention are parts by weight.
[0047] The technical solution of the present invention is further illustrated by the following embodiments.
[0048] Example 1
[0049] Weigh 300 parts of sulphoaluminate cement and 150 parts of water by weight;
[0050] Pour sulphoaluminate cement and water into a mixer, stir at a constant speed of 2000 r / min for 60 s, and pour out immediately after mixing evenly to obtain a sulphoaluminate cement control sample, sample number 1.
[0051] Example 2
[0052] Weigh 300 parts of sulphoaluminate cement, 150 parts of water, and 0.15 parts of sodium gluconate by weight;
[0053] Pour sodium gluconate and water into a beaker and stir until the sodium gluconate is completely melted to obtain a sodium gluconate solution; pour the sodium gluconate solution and sulphoaluminate cement into a mixer, stir at a constant speed of 2000 r / min for 60 s, pour out immediately after mixing evenly, and obtain a sulphoaluminate cement control sample, sample number 2.
[0054] Example 3
[0055] Weigh 270 parts of sulphoaluminate cement, 150 parts of water, 30 parts of superfine powder, and 0.15 parts of sodium gluconate by weight;
[0056] Pour sodium gluconate and water into a beaker and stir until the sodium gluconate is completely melted to obtain a sodium gluconate solution. Pour the ultrafine powder and sulfoaluminum cement into a mixer and stir at a constant speed of 2000r / min for 10s. After stirring evenly, add the sodium gluconate solution and stir at a constant speed for 60s in the mixer. After mixing evenly, pour out immediately to obtain sulfoaluminate cement repair material, sample number 3.
[0057] Example 4
[0058] Weigh 240 parts of sulphoaluminate cement, 150 parts of water, 60 parts of superfine powder, and 0.15 parts of sodium gluconate by weight;
[0059] Pour sodium gluconate and water into a beaker and stir until the sodium gluconate is completely melted to obtain a sodium gluconate solution. Pour the ultrafine powder and sulfoaluminum cement into a mixer and stir at a constant speed of 2000r / min for 10s. After stirring evenly, add the sodium gluconate solution and stir at a constant speed for 60s in the mixer. After mixing evenly, pour out immediately to obtain sulfoaluminate cement repair material, sample number 4.
[0060] Example 5
[0061] Weigh 210 parts of sulphoaluminate cement, 150 parts of water, 90 parts of superfine powder, and 0.15 parts of sodium gluconate by weight;
[0062] Pour sodium gluconate and water into a beaker and stir until the sodium gluconate is completely melted to obtain a sodium gluconate solution. Pour the ultrafine powder and sulfoaluminum cement into a mixer and stir at a constant speed of 2000r / min for 10s. After stirring evenly, add the sodium gluconate solution and stir at a constant speed for 60s in the mixer. After mixing evenly, pour out immediately to obtain sulfoaluminate cement repair material, sample number 5.
[0063] Example 6
[0064] Weigh 300 parts of sulphoaluminate cement, 150 parts of water, and 0.3 parts of sodium gluconate by weight;
[0065] Pour sodium gluconate and water into a beaker and stir until the sodium gluconate is completely melted to obtain a sodium gluconate solution. Pour the ultrafine powder and sulfoaluminum cement into a mixer and stir at a constant speed of 2000r / min for 10s. After stirring evenly, add the sodium gluconate solution and stir at a constant speed for 60s in the mixer. After mixing evenly, pour out immediately to obtain sulfoaluminate cement repair material, sample number 6.
[0066] Example 7
[0067] Weigh 300 parts of sulphoaluminate cement, 150 parts of water, and 0.45 parts of sodium gluconate by weight;
[0068] Pour sodium gluconate and water into a beaker and stir until the sodium gluconate is completely melted to obtain a sodium gluconate solution. Pour the ultrafine powder and sulfoaluminum cement into a mixer and stir at a constant speed of 2000r / min for 10s. After stirring evenly, add the sodium gluconate solution and stir at a constant speed for 60s in the mixer. After mixing evenly, pour out immediately to obtain sulfoaluminate cement repair material, sample number 7.
[0069] Example 8
[0070] Weigh 270 parts of sulphoaluminate cement, 150 parts of water, 30 parts of superfine powder, and 0.45 parts of sodium gluconate by weight;
[0071] Pour sodium gluconate and water into a beaker and stir until the sodium gluconate is completely melted to obtain a sodium gluconate solution. Pour the ultrafine powder and sulfoaluminum cement into a mixer and stir at a constant speed of 2000r / min for 10s. After stirring evenly, add the sodium gluconate solution and stir at a constant speed for 60s in the mixer. After mixing evenly, pour out immediately to obtain sulfoaluminate cement repair material, sample number 8.
[0072] Example 9
[0073] Weigh 240 parts of sulphoaluminate cement, 150 parts of water, 60 parts of superfine powder, and 0.45 parts of sodium gluconate by weight;
[0074] Pour sodium gluconate and water into a beaker and stir until the sodium gluconate is completely melted to obtain a sodium gluconate solution. Pour the ultrafine powder and sulfoaluminum cement into a mixer and stir at a constant speed of 2000r / min for 10s. After stirring evenly, add the sodium gluconate solution and stir at a constant speed for 60s in the mixer. After mixing evenly, pour out immediately to obtain sulfoaluminate cement repair material, sample number 9.
[0075] Example 10
[0076] Weigh 240 parts of sulphoaluminate cement, 150 parts of water, 60 parts of superfine powder, and 0.6 parts of sodium gluconate by weight;
[0077] Pour sodium gluconate and water into a beaker and stir until the sodium gluconate is completely melted to obtain a sodium gluconate solution. Pour the ultrafine powder and sulfoaluminum cement into a mixer and stir at a constant speed of 2000r / min for 10s. After stirring evenly, add the sodium gluconate solution and stir at a constant speed for 60s in the mixer. After mixing evenly, pour out immediately to obtain sulfoaluminate cement repair material, sample number 10.
[0078] Embodiment 11
[0079] Weigh 210 parts of sulphoaluminate cement, 150 parts of water, 90 parts of superfine powder, and 0.6 parts of sodium gluconate by weight;
[0080] Pour sodium gluconate and water into a beaker and stir until the sodium gluconate is completely melted to obtain a sodium gluconate solution. Pour the ultrafine powder and sulfoaluminum cement into a mixer and stir at a constant speed of 2000r / min for 10s. After stirring evenly, add the sodium gluconate solution and stir at a constant speed for 60s in the mixer. After mixing evenly, pour out immediately to obtain sulfoaluminate cement repair material, sample number 11.
[0081] Example 12
[0082] Weigh 210 parts of sulphoaluminate cement, 150 parts of water, 90 parts of superfine powder, and 0.75 parts of sodium gluconate by weight;
[0083] Pour sodium gluconate and water into a beaker and stir until the sodium gluconate is completely melted to obtain a sodium gluconate solution. Pour the ultrafine powder and sulfoaluminum cement into a mixer and stir at a constant speed of 2000r / min for 10s. After stirring evenly, add the sodium gluconate solution and stir at a constant speed for 60s in the mixer. After mixing evenly, pour out immediately to obtain sulfoaluminate cement repair material, sample number 12.
[0084] Example 13
[0085] Weigh 100 parts of ordinary Portland cement and 50 parts of water by weight;
[0086] Ordinary Portland cement was poured into a mixer and stirred at a constant speed of 2000 r / min for 10 seconds. After stirring evenly, sodium gluconate solution was added and stirred at a constant speed for 60 seconds. After mixing evenly, the mixture was poured out immediately to obtain Portland cement slurry, sample number 13.
[0087] Embodiment 14
[0088] Weigh 90 parts of sulphoaluminate cement, 50 parts of water and 10 parts of superfine powder by weight;
[0089] Ordinary Portland cement and superfine powder were poured into a mixer and stirred at a constant speed of 2000 r / min for 10 seconds. After stirring evenly, sodium gluconate solution was added and stirred at a constant speed for 60 seconds. After mixing evenly, the mixture was poured out immediately to obtain Portland cement slurry, sample number 14.
[0090] Embodiment 15
[0091] Weigh 80 parts of sulphoaluminate cement, 50 parts of water, and 20 parts of superfine powder by weight;
[0092] Ordinary Portland cement and superfine powder were poured into a mixer and stirred at a constant speed of 2000 r / min for 10 seconds. After stirring evenly, sodium gluconate solution was added and stirred at a constant speed for 60 seconds. After mixing evenly, the mixture was poured out immediately to obtain Portland cement slurry, sample number 15.
[0093] Example 16
[0094] Weigh 70 parts of sulphoaluminate cement, 50 parts of water, and 30 parts of superfine powder by weight;
[0095] Ordinary Portland cement and superfine powder were poured into a mixer and stirred at a constant speed of 2000 r / min for 10 seconds. After stirring evenly, sodium gluconate solution was added and stirred at a constant speed for 60 seconds. After mixing evenly, the mixture was poured out immediately to obtain Portland cement slurry, sample number 16.
[0096] Performance Testing
[0097] 1. Initial setting time and final setting time
[0098] The initial setting time and final setting time of samples 1-12 were measured according to the method in GB / T1346-2001 "Test Method for Water, Setting Time and Stability of Cement Standard Consistency". The results are shown in Table 2. The comparison bar chart of the initial setting and final setting time of each sample is shown in Figure 1 .
[0099] Table 2 Initial setting time and final setting time of samples 1-12
[0100]
[0101]
[0102] From Table 2 and Figure 1It can be seen that sample 1 did not add sodium gluconate and ultrafine powder, and the setting time was shorter; by comparing samples 2, 6, and 7, it was found that with the increase in the amount of sodium gluconate, the setting time of sulphoaluminate cement gradually increased, indicating that sodium gluconate has an obvious retarding effect on sulphoaluminate cement; when the same amount of sodium gluconate was added, the setting time of sulphoaluminate cement in samples 2, 3, and 4 gradually decreased with the increase in the amount of ultrafine powder, indicating that the ultrafine powder has a promoting effect on the setting time of sulphoaluminate cement.
[0103] By adjusting the amount of ultrafine powder and sodium gluconate, the setting time of sulphoaluminate cement can be adjusted, such as samples 8, 9, 10, 11, and 12. In the actual construction process, according to different construction requirements and construction environments, the setting time can be adjusted by adjusting the addition of different proportions of sodium gluconate and ultrafine powder, thereby making the use scenarios of silicon-aluminum cement-based repair materials more diversified.
[0104] 2. SEM test
[0105] The raw materials sulphoaluminate cement and ultrafine powder used in the preparation process of each embodiment were subjected to SEM test, and the test results are shown in Figure 2-Figure 5 ,in Figure 2 and Figure 3 The following are SEM microscopic images of raw material sulphoaluminate cement magnified at 5000 times and 1000 times respectively. Figure 4 and Figure 5 These are SEM microscopic morphology images of the raw material ultrafine powder magnified at 5000 times and 1000 times respectively.
[0106] Depend on Figure 2-Figure 5 It can be seen that the particle size of ultrafine powder is smaller than that of sulphoaluminate cement.
[0107] 3. Particle size distribution test
[0108] The particle size distribution test was performed on the raw materials sulphoaluminate cement and ultrafine powder used in the preparation process of each embodiment. Figure 6 is the particle size distribution curve of raw material sulphoaluminate cement, Figure 7 This is the particle size distribution curve of the raw material ultrafine powder.
[0109] Depend on Figure 6 and Figure 7 It can be seen that the particle size of ultrafine powder is much smaller than that of sulphoaluminate cement. On the one hand, it can play its own dense filling role, optimize the particle grading of the repair material, and reduce the porosity of the repair material itself; on the other hand, the addition of ultrafine mineral admixtures can replace the filling water in the pores of the repair material. The replaced free water can increase the thickness of the lubricating layer on the surface of the raw material particles of the repair material and improve the workability of the repair material.
[0110] 4. Porosity
[0111] The pore structure is closely related to the strength and durability of the repair material. The porosity of the repair materials 28d of samples 7, 8, 10 and 11 prepared in the examples was measured by mercury intrusion testing. Figure 8 As shown. Figure 8 It can be seen that in the samples cured for 28 days, with the increase of the dosage of ultrafine mineral admixture, the total pore volume of the samples showed a downward trend. The porosity of samples 7, 8, 10 and 11 were 10.2%, 9.7%, 8.1% and 7.8%, respectively. The total pore volume of the samples added with ultrafine mineral admixture decreased by 0.5%, 2.1% and 2.4% respectively compared with sample 7.
[0112] 5. Hydration Exothermicity
[0113] The effects of the samples prepared in Examples 13-16 on the heat release of cement hydration and the heat release rate of hydration were tested. Fig. 9 (a) The effect of the samples prepared in Examples 13-16 on the heat release of cement hydration, as shown in Fig. 9 As shown in (a), the addition of ultrafine mineral admixtures reduces the hydration heat release of cement-based materials. When the ultrafine mineral admixture dosage is 20% (the proportion of ultrafine powder to the total mass of sulphoaluminate cement + ultrafine powder), the hydration heat release of the sample is the lowest, which is 203.68 J / g. When the ultrafine mineral admixture is reduced to 10% or increased to 30%, the hydration heat release of the sample increases slightly, which are 221.79 J / g and 211.32 J / g, respectively, but are both lower than the blank group's 234.85 J / g. The hydration heat release of samples with 10%, 20% and 30% ultrafine mineral admixtures within 3 days decreased by 5.57%, 13.3% and 10.02% respectively compared with the hydration heat release of the blank group (Example 13).
[0114] Fig. 9 (b) The effect of the samples prepared in Examples 13-16 on the heat release rate of cement hydration, as shown in Fig. 9 As shown in (b), there are three exothermic peaks in the early hydration of cement, which are dissolution exothermic peak, silicon phase reaction peak and aluminum phase reaction peak in order of appearance time. Fig. 9(b) It can be seen that the addition of ultrafine fractions increases the hydration heat release rate of cement and shortens the interval between the silicon phase peak and the aluminum phase peak. The ultra-high specific surface area of the ultrafine fraction can provide nucleation sites for the generation of hydration products and promote the cement hydration reaction. The appearance time of the aluminum phase reaction peak is advanced. Compared with the blank group (Example 13), the appearance time of the aluminum phase reaction peak is advanced by about 1h at the fastest, and the peak height of the aluminum phase reaction peak increases. The aluminum phase in the ultrafine fraction participates in the reaction, and the CSH gel generated by the reaction of active silicon and active aluminum in the ultrafine fraction with calcium hydroxide can adsorb sulfate ions in the system, thereby promoting the hydration reaction of C3A and increasing the peak height of the aluminum phase reaction peak. The peak height of the silicon phase reaction peak is reduced, and a "peak clipping phenomenon" occurs, and the time of appearance of the silicon phase reaction peak is delayed. The incorporation of ultrafine mineral admixtures leads to a reduction in the amount of cement used, resulting in a reduction in the silicon phase content in the system, thereby leading to a weakening of the peak height.
[0115] 6. Compressive strength
[0116] The compressive strength of the repair materials of samples 7, 8, 10 and 11 prepared in Example 1 was tested. The test results are shown in Fig.10 .like Fig.10 As shown in Figures 7, 8, 10 and 11, the ultrafine powder can significantly improve the strength of sulphoaluminum cement mortar, and the ultrafine powder with a dosage of 30% can maximize the strength improvement of the repair mortar.
[0117] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A sulphoaluminate cement repair material, characterized in that: The raw materials are composed of sulphoaluminate cement, sodium gluconate, ultrafine powder and water, wherein the mass ratio of the sulphoaluminate cement to the ultrafine powder is (7-9): (1-3), the sodium gluconate accounts for 0.05%-0.25% of the total mass of the sulphoaluminate cement and the ultrafine powder; the amount of water is 50% of the total mass of the sulphoaluminate cement and the ultrafine powder; The specific surface area of the ultrafine powder is 700-900m 2 / kg, median diameter ≤5μm; The composition and mass percentage of the ultrafine powder are CaO: 21.37%, SiO2: 27.52%, Al2O3: 20.18%, Fe2O3: 2.12%, SO3: 3.053%, MgO: 3.51%, TiO2: 0.797%, P2O5: 0.153%, K2O: 0.504% and Na2O: 0.3%; The raw materials of the ultrafine powder include mineral powder, fly ash and gypsum; The preparation method of the sulphoaluminate cement repair material comprises the following steps: Weigh the required sulphoaluminate cement, sodium gluconate, superfine powder and water according to the mass ratio, dissolve the sodium gluconate in water to obtain a sodium gluconate solution, mix the superfine powder and sulphoaluminate cement evenly, add them to the sodium gluconate solution, stir evenly, and obtain the sulphoaluminate cement repair material.
2. The sulphoaluminate cement repair material according to claim 1, characterized in that: The mass ratio of the sulphoaluminate cement to the superfine powder is 7:3, and the sodium gluconate accounts for 0.25% of the total mass of the sulphoaluminate cement and the superfine powder.
Citation Information
Patent Citations
Retarder applicable to sulphate aluminum cement
CN105000819A
A retarder suitable for sulfoaluminate cement
CN108083674B
Ocean engineering repair mortar and preparation method thereof
CN110746165A
Retarder for adjusting initial setting time of sulphoaluminate cement as well as preparation method and use method of retarder
CN112851185A